Negotiating Between Identities: Indonesia’s Chinese-Language Newspapers in the Post-New Order Era - Yuhao Wen (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2018)
This study aims to provide a description of Chinese-Indonesian identity in the post-New Order era. Under the previous authoritarian regime, public expression of Chinese identity in all social fields, such as culture, language and politics, was officially suppressed by the government through its assimilation policy. A person could be Chinese or Indonesian, but not both. Since the collapse of the New Order government in 1998, Indonesia has begun the process of democratization, and the old Indonesian identity and cultural heritage of Indonesia has been "liberated". Now there is an urgent need to re-examine the identity of the Chinese. One channel for expressing Chinese ethnic identity is through ethnic media, such as Chinese newspapers which this paper will focus on. Based on this context, this paper aims to see what Chinese-Indonesian identities are presented in Chinese-language Indonesian newspapers in the post-New Order era by analyzing their reporting and discussion regarding main domestic political events.Bahasa Abstrak: Penelitian ini bertujuan untuk memberikan penggambaran identitas orang Tionghoa-Indonesia di era pasca-Orde Baru. Di bawah rezim otoriter, ekspresi publik dengan identitas Tionghoa di semua bidang sosial, seperti budaya, bahasa dan politik, ditekan secara resmi oleh pemerintah seiring dengan kebijakan asimilasi. Seseorang bisa menjadi orang Tionghoa atau orang Indonesia, tetapi tidak keduanya. Sejak runtuhnya pemerintahan Orde Baru pada tahun 1998, Indonesia telah memulai proses demokratisasi, dan identitas lama serta warisan budaya Tionghoa-Indonesia telah "dibebaskan". Sekarang ada kebutuhan mendesak untuk memeriksa kembali identitas orang Tionghoa. Satu saluran untuk mengekspresikan identitas etnis Tionghoa adalah melalui media etnis, seperti surat kabar berbahasa Mandarin - sebagaimana yang akan difokuskan oleh makalah ini. Berdasarkan konteks ini, makalah ini bertujuan untuk melihat apa identitas orang Tionghoa-Indonesia yang disajikan dalam surat kabar Indonesia berbahasa Mandarin di masa pasca-Orde Baru, dengan menganalisa pelaporan dan diskusi mereka mengenai peristiwa politik domestik yang utama.